Beyond the Cover: An In-Depth Analysis of the Practicality of an English Textbook by the Indonesian Government Post Pandemic Covid-19 - Nur Hidayati, Diyah; Kusumawati , Eny (Universitas Tidar, 2023)
For teaching and student learning, textbooks are a vital and widely used resource. The purpose of this study was to assess the unit design in